Gender Segregation in Regional Labour Market: Evidence from South Sumatra Province, Indonesia - Azwardi Azwardi; Yunisvita Yunisvita; Sri Andaiyani; Sukanto Sukanto; Arika kurniawan (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2023)
This study aims to examine gender segregation and type of work to measure the overall of segregation and the segregation of several population subgroups, namely education, age, wages, working hours, and area of residence. The approach that used is the measurement of segregation Multi-group that refers to. Research finds that working women have relatively high contribution against the segregation of gender as a whole, in the case of the level of education shows female and male segregated by level of education. While it is for the subgroup (type of work) workers young and advanced age, workers with a group of wages high and workers part-time has contributed that high against segregation type of work as a whole